Village Fund Management: A Foucauldian Perspective - Alexander Anggono; - Tarjo; Beni Pradinata (InFestasi, 2020)
The village fund was introduced in 2014 to stimulate development in villages all over Indonesia.  However, the special task force of the village fund in the mid of 2017 solely had received 10,000 complaints regarding suspicion of misuse of the village fund, which resulted in 200 village officials end up in jail. Therefore, this study is to explore many aspects affecting the processes of planning and establishing of village budget in a village located at Madura.     A qualitative approach is applied in this study to enable researchers to explore many aspects of the management of the village fund.  The findings of this study indicate that the Musrenbangdes as a tool in the planning stage were intervened by the head of the village without considering the interests of local society. Consequently, development proposals contained in the Musrenbangdes, which later were elaborated in the RPJMDesa as mid-term programs and the RKPDesa as short-term programs, were determined by the head of the village and his officials. Meanwhile, the head of the village is not equipped to handle the planning and budgeting process of the village fund.  Hence, the head of the village placed his right-hand man as a coordinator to manage the village fund, resulting in a lack of transparency in the management of the fund.